Evaluation of diabetic retinopathy in adults with type 1 diabetes at Ceará state (Research, Society and Development, 2020)
It is estimated that there are more than 30 thousand people with type 1 diabetes mellitus (DM1) in Brazil. Among the complications, diabetic retinopathy (DR) is one of the most prevalent, affecting up to 50% of DM1 patients in some populations. This study aims to estimate the prevalence of DR in DM1 or Latent autoimmune diabetes in adults (LADA), in addition to assessing risk factors involved. A cross-sectional study was carried out evaluating 81 patients over 18 years of age and diagnosed with long-term type 1 DM. Demographic, clinical and laboratory aspects were assessed using a structured questionnaire. Ophthalmological examination data were collected from medical records. We observed a 33% prevalence of DR in patients with DM1 in the state of Ceará. This complication was more associated with older patients (p = 0.004), longer DM1 time (p